SINTESIS KONSEPTUAL STRUKTUR DAN FUNGSI TUMBUHAN ANGIOSPERMAE - Dian Christine; Meyra An Najmi; Siti Aisyah; Afridha Laily Alindra (STKIP Subang, 2026)
Understanding the structure and function of angiosperms is a key component of elementary school science education that supports the development of science literacy from an early age. However, the low science literacy scores of Indonesian students in PISA 2022 indicate the need for a more integrated and evidence-based teaching approach. This study aims to systematically synthesize the latest research findings on the structure and function of Angiosperms to identify forms of conceptual integration relevant to elementary school science content. The method used is a Systematic Literature Review (SLR) following the PRISMA 2020 guidelines, with the Scopus database searched for articles published between 2021 and 2026. Of the 11 identified articles, 10 met the inclusion criteria and were analyzed in depth. The synthesis results identified three main forms of concept integration: (1) structure-function integration, which links plant organ anatomy to their roles in physiological processes; (2) contextual integration, which connects Angiospermae concepts to natural phenomena in students’ learning environments; and (3) integration based on current scientific findings, which utilizes the latest Scopus literature as a source of authentic content. These three approaches have consistently proven relevant for improving elementary school students’ conceptual understanding and science literacy This study recommends the use of conceptual synthesis based on indexed scientific literature as a framework for developing integrated, contextual, and evidence-based science teaching materials.